Real-Time Assessment of Stress and Stress Response Using Digital Phenotyping: A Study Protocol - Egger, Stephan T.; Knorr, Marius; Bobes, Julio; Bernstein, Abraham; Seifritz, Erich; Vetter, Stefan (Frontiers in Digital Health, 2020)
Background: Stress is a complex phenomenon which may have a negative influence on health and wellbeing; consequently, it plays a pivotal role in mental health. While the incidence of mental disorders has been continuously rising, development of prevention and treatment methods has been rather slow. Through the ubiquitous presence of smartphones and wearable devices, we have the possibility to monitor stress parameters in everyday life. However, the reliability and validity of such monitoring are still unsatisfactory. Methods: Aim of this trial is to find a relationship between psychological stress, saliva cortisol levels on the one hand and physiological parameters measured by smartphone in combination with a commercially available wearable device on the other. The study will we conduct in two settings. The first uses Ecological Momentary Assessment (EMA) for the measurement of challenging and stressful situations during a whole week; the second uses digital Phenotyping during the exposition of the participants to a controlled stress situation, with the Trier Social Stress Test (TSST). EMA using a smartphone application allows the participants to keep a diary for a whole week of their activities, wellbeing, sleep; as well as the timely recording of subjective experiences and behaviour during difficult and stressful situations they encounter. Through wearable devices, physiological parameters will be continuously monitored. Saliva cortisol samples will repeatedly be taken. On the fifth day, the participants will undergo the TSST to induce psycho-biological stress in a controlled laboratory setting; before, during and after the TSST psychological stress, saliva cortisol levels and physiological parameters will be continuously measured. Discussion: We hope to identify valid and reliable digital biomarkers for stress and stress reaction. Further, we hope to find a way of early detection of stress in order to evolve new opportunities for interventions reducing stress. That may once allow the finding of new ways to treat and prevent mental disorders.